Islamic Philanthropy on Social Media in Youth Volunteering Movements - Saidah, Musfiah; Ulfahadi, Rizki; Maylafayzah, Hilya (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2023)
Islamic philanthropy through social media is a form of community participation in the youth volunteering movement. Social media is used to spread information, raise funds, attract volunteers, and collaborate with philanthropic institutions. Islamic philanthropy through social media can help in building a caring and sharing society, as well as strengthening the spirit of humanity and expanding the reach of philanthropic activities. Islamic philanthropy through social media has an important role in helping youth to build a more caring and friendly society. Youth volunteering movements are in dire need of support from the community, and Islamic philanthropy through social media can help overcome obstacles and strengthen the spirit of humanity. This research method uses a qualitative approach with a literature study method. Social media is becoming an effective tool for achieving the goals of the youth volunteering movement, by helping to disseminate information, raise funds, attract volunteers, and collaborate with philanthropic institutions. Therefore, Islamic philanthropy through social media is very important and can help youth in achieving their vision of building a better society.